Nitroglycerin induced syncope occurs in subjects with delayed phase shift of baroreflex action - Melenovsky, Vojtech; Wichterle, Dan; Malik, Jan; Simek, Jan; Hradec, Jaromir; Ceska, Richard; Malik, Marek (Pacing and clinical electrophysiology, 2002)
Nitroglycerin (NTG) administration occasionally leads to syncope due to severe hypotension and bradycardia. This reaction resembles neurocardiogenic syncope but it may occur when the patient is in the supine position. To address the possible role of prevailing autonomic tone and baroreflex control in precipitation of NTG induced syncope, continuous noninvasive blood pressure and an ECG were taken shortly before NTG application in the supine position. Frequency-domain measures of heart rate variability (HRV) and noninvasive indices of baroreflex were compared between subjects who did (n = 6) and did not (n = 41) develop syncope after NTG. Both groups differed only in the phase shift (P(CR)) between oscillations of blood pressure and heart rate during controlled respiration (0.1 Hz). P(CR) was significantly delayed in subjects who developed syncope than in controls (- 99.3+/-14.1 vs -65.5+/-27.0 degrees, P = 0.002). Thus, subjects with prolonged P(CR) are prone to NTG induced syncope because of increased lagging and, consequently, less stable baroreflex control.
Keywords: supinační poloha; Humans; lidé středního věku; Blood Pressure Determination; Electrocardiography; dospělí; Heart Rate; Nitroglycerin; lidé; baroreflex; bradykardie; Baroreflex; Syncope; Supine Position; Adult; Bradycardia; krevní tlak; Male; srdeční frekvence; Middle Aged; synkopa; hypotenze; Hypotension; mužské pohlaví; nitroglycerin; Blood Pressure; měření krevního tlaku; elektrokardiografie